Negative impacts of riba banking on performance of Islamic banking - Htay, Sheila Nu Nu; Abdul Aziz, Mohammed Zahid; Hamat, Musthpha (2011)
Islamic banking is now an established part of many nations’ banking system so much so it is said to be operating in a dual system alongside conventional banking. The duality of the system in particular is emphasised in Malaysia where the duality is even acknowledged by the nation’s central banking legislation. This duality however is not such an innocuous situation and is suspected by the researcher to be a principal reason for many of the weaknesses to be found in Islamic banking today. That Islamic banking is criticised for many deficiencies is a widespread phenomenon these days. Amongst the many criticisms of Islamic banking in a dual system includes it being a mirror image of conventional banking delivering products and services not much different from its conventional counterpart; it delivers products which are tenuous in terms of compliance with Shariah; it does not uphold the demands of Maqasid Shariah in failing to cater to financing for the poorer section of the society, and in failing to aid the wider and more equitable distribution of wealth; it is not attractive in competing for deposits with conventional banks; it assumes risks which should not be found in an interest free environment; and it manages risk as if it is a money lender. The reasons for these deficiencies have been attributed to it being too focussed on debt financing products, the weaknesses of Islamic bankers, and the impiety of the ummah. No studies have sought to identify the coexistence of conventional banking as a factor directly contributing to these weaknesses and deficiencies of Islamic banking. No studies have examined the environment Islamic banking is expected to be operating in as compared to the environment it found itself in. No studies have examined whether the regulatory measures imposed on conventional banking is correct when similarly imposed on Islamic banking. This study aims to fill that gap, to determine and if proven, to articulate that conventional banking is negatively impacting on the performance of Islamic banking, in particular on Islamic banking’s ability to uphold true compliance with Shariah. This study finds that in reality, the impacts of the riba banking on the performance of Islamic banks are negatives. It is hoped that this study will trigger similar studies to further prove its findings. It is the unashamed hope of the researcher that one day Muslim nations can bury riba banking and build on its ashes a sole and single Islamic banking system that upholds and embodies the true demands of the Quran and Sunnah.